Model Time Series untuk Prediksi Jumlah Kasus Infeksi Coronavirus (Covid-19) di Sulawesi Selatan - Asrirawan, Asrirawan; Seppewali, Andi; Fitriyani, Nurul (Universitas Islam Negeri Alauddin Makassar, 2020)
Since it was declared a pandemic outbreak, the COVID 19 virus has become one of the main focuses of countries in the world in efforts to prevent the spread of the virus, including Indonesia. The areas of greatest severity in Indonesia include Jakarta, East Java, West Java and South Sulawesi. South Sulawesi Province is recorded as the largest area exposed to the COVID 19 pandemic outside Java Island. Predicting the number of COVID 19 cases is an alternative in preventing the spread through making government policies based on predictive data. This article presents a predictive model for the number of COVID 19 cases based on the ARIMA, Holt Winters and Nonlinear Autoregressive Neural Network (NAR-NN) Model. The results of the analysis show that the ARIMA Model (1,1,1) has a better level of prediction accuracy than the HW and NAR-NN models based on the MAPE criteria. Meanwhile, for the RMSE, MAE and MPE criteria, the NAR-NN model is better than others.